Persistence and removal of trace organic compounds in centralized and decentralized wastewater treatment systems. (January 2022) - Mladenov, Natalie; Dodder, Nathan G.; Steinberg, Lauren; Richardot, William; Johnson, Jade; Martincigh, Bice S.; Buckley, Chris; Lawrence, Tolulope; Hoh, Eunha
Abstract: The persistence of trace organic chemicals in treated effluent derived from both centralized wastewater treatment plants (WWTPs) and decentralized wastewater treatment systems (DEWATS) is of concern due to their potential impacts on human and ecosystem health. Here, we utilize non-targeted analysis (NTA) with comprehensive two-dimensional gas chromatography coupled with time of flight mass spectrometry (GC × GC/TOF-MS) to conduct an evaluation of the common persistent and removed compounds found in two centralized WWTPs in the USA and South Africa and one DEWATS in South Africa. Overall, removal efficiencies of chemicals were similar between the treatment plants when they were compared according to the number of chemical features detected in the influents and effluents of each treatment plant. However, the DEWATS treatment train, which has longer solids retention and hydraulic residence times than both of the centralized WWTPs and utilizes primarily anaerobic treatment processes, was able to remove 13 additional compounds and showed a greater decrease in normalized peak areas compared to the centralized WWTPs. Of the 111 common compounds tentatively identified in all three influents, 11 compounds were persistent in all replicates, including 5 compounds not previously reported in effluents of WWTPs or water reuse systems. There were no significant differences among the physico-chemical properties of persistent and removed compounds, but significant differences were observed among some of the molecular descriptors. These results have important implications for the treatment of trace organic chemicals in centralized and decentralized WWTPs and the monitoring of new compounds in WWTP effluent. Highlights: Non-targeted analysis (NTA) identified 111 common WWTP influent compounds. 11 of the common influent compounds were persistent in the studied WWTP effluents. Anaerobic treatment reduced chemical peak areas more than conventional treatment. NTA revealed 5 new compounds not previously reported in WWTP effluent. Physico-chemical properties did not differ among persistent and removed compounds.